Influence of aspect ratio on flexural behavior of reinforced self-compacting concrete beams. (December 2022) - Raju, Sumathy; Arulpandian, V.; Avudaiappan, Siva; Amran, Mugahed; Fediuk, Roman; Vatin, Nikolai; Flores, Erick Saavedra; Mosaberpanah, Mohammad Ali
Abstract: Concrete is a quasi-brittle material whose basic mechanical properties are size-dependent. Due to simple substitution in profoundly congested support structures without experiencing any consolidation, non-segregation property, and smooth finishing, it could be an exceptionally great choice in the concrete industry. The research object is the size effect on the flexural behavior of reinforced self-compacting concrete (SCC) beams by varying depth, length, and span. The length to depth ratio (aspect ratio) was 3.88, 5.38, 8.75, 11.5, and 15.38. SCC trial mixes were technologically advanced using FA (FA) as filler material and conplast SP430 as Super-plasticizer (SP). The workability properties were determined via the T50 cm slump flow, slump flow, U-box, V-funnel, J-ring, and L -box tests. FA (30%) with SP (1.9%) is satisfied with all the requirements of SCC as per EFNARC guidelines, and the designed compressive strength of concrete was obtained as 30 MPa. A total of six beams with various sizes, such as depths of 100 mm, 150 mm, and 200 mm, and lengths of 900, 1700, and 2200 mm, were cast with 1.2% tensile reinforcement bars. Based on the depth effect of beams, the load-deflection behavior, flexural strength, ductility index, and stiffness were studied. It is revealed that there is a decrease in strength properties by increasing the depth of beams during the static load conditions. Beams with a length equal to 1700 mm reached the best performance. It was also found the most advantageous l/d proportion, in terms of mechanical performance, is equal to 5.38.